Optimalisasi Pengembangan Anak Panti Asuhan melalui Event Facena Love Lab Mahar Agung - Ericha Florenzia Matahurila; Sugito (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2025)
Community service is part of the Tri Dharma of Higher Education, which aims to make a real contribution to improving the quality of life in the community. Children in orphanages are a social group that requires ongoing support, not only in meeting basic needs but also in developing character, self-confidence, and social skills. This community service activity focuses on optimizing the development of children in orphanages through the Facena Love Lab event organized by Mahar Agung. The goal of this activity is to increase self-confidence, social interaction, and develop the potential of children in orphanages through an educational and creative approach. The empowerment method used is a descriptive qualitative approach with a participatory strategy, encompassing the planning, implementation, and evaluation stages. The activity took the form of an event that included motivational sessions, educational games, art activities, and group activities that actively involved children in orphanages. The empowerment results showed that children in orphanages experienced increased courage in interactions, self-confidence, and the ability to work together in groups. Furthermore, this activity also fostered the values ​​of responsibility, discipline, and togetherness. The Facena Love Lab event has proven to be an effective and enjoyable non-formal learning tool in supporting the development of children in orphanages. This activity is expected to become a model for event-based support that can be implemented sustainably